Comparative study of the prevalence, clinical features, sensitisation profiles and risk factors for bronchial asthma between elderly and young adults in Cova da Beira - Moreira, Sónia Manuela Rodrigues (2010)
Background: Bronchial asthma is one of the most common allergic diseases worldwide. Very few studies have analysed whether the prevalence of asthma decreases with age. Therefore, the aim of the present study was to compare the prevalence, pattern of aeroallergen sensitization and clinical features of bronchial asthma between elderly and young adults. In addition, we also wanted to analyse possible risk factors for the development of asthma. Methods: This study followed a cross-sectional design. A standardised allergy and asthma questionnaire and skin prick tests (SPT) were carried out in all volunteers. The study population included two groups of individuals: elderly (aged 65 years and older) and young adults (aged between 18-35 years) from Beira Interior. The sample was selected by simple randomization, after calculating a confidence interval of 95% and an estimated error below 5%. Statistical analysis was carried out using Chi-square tests, Mann-Whitney U test, univariate regression analysis, binary logistic regression analysis and Odds Ratio. A p value less than 0.05 was considered statistically significant. All patients signed a written informed consent and the study was approved by the Regional Health Authority Ethics Committee. Results: A total sample of 1460 volunteers was included. Thus far, we have analyzed a total of 27.6% of elderly volunteers in the Health Care Centre (median age = 73 years; 41.5% males) and 14.1% of the young group (median age = 28 years; 44.2% males). A short questionnaire was applied by telephone to 11% of the total sample. We found significant differences in the prevalence of bronchial asthma between elderly and young adults (19.7% vs 29.4%, respectively; p=0.02; Chi-square test). In addition, the prevalence of atopic bronchial asthma was also significantly lower in elderly than in young adult patients (32.1% vs 57.1%, respectively; p=0.02, Chi-square test). Both groups were mostly sensitised to Dermatophagoides pteronyssinus and Dermatophagoides farinae. Significant differences were found in terms of sensitisation to grass pollens amongst elderly and young patients (11.8% vs 70.8%, respectively; p=0.0006, Chi-square test). The majority of the asthmatic patients were sensitised to more than one allergen. Finally, differences were observed in terms of risk factors for bronchial asthma between both groups, with gender as a significant risk factor in elderly patients and concomitant rhinitis in young patients. The presence of rhinitis augmented the risk of having asthma 3.2 times, in the group of young adults.